Flow Cytometry Analysis of Intracellular VASP Phosphorylation for the Assessment of Activating and Inhibitory Signal Transduction Pathways in Human Platelets - Schwarz, Ulrike R.; Geiger, Jörg; Walter, Ulrich; Eigenthaler, Martin (Thrombosis and Haemostasis, 1999)
Increased platelet adhesion or aggregation are key events in the pathogenesis of cardiovascular diseases. Exact determination of the platelet activation state is essential to recognize, prevent, and treat cardiovascular complications due to platelet dysfunction. Initial phases of platelet activation and inhibition are characterized by phosphorylation of specific intracellular proteins. However, methodological problems often prevent analysis of platelet protein phosphorylation under clinical conditions. A novel flow cytometry-based method using a phosphorylation-specific antibody was developed for fast and easy quantification of the phosphorylation state of a specific intracellular platelet protein. This method was used to analyze various platelet receptors and their intracellular signaling which may be impaired in genetic or acquired disorders or altered due to therapeutic interventions. In a first clinical application, the inhibitory effects of ticlopidine and clopidogrel on the platelet P2YAC ADP receptor were monitored.Abbreviations: ADP: adenosine 5’-diphosphate; cAMP: cyclic adenosine-3’,5’-monophosphate; cGMP: cyclic guanosine-3’,5’-monophosphate; HUVECs: human umbilical vein endothelial cells; MAPK: mitogen-activated protein kinase; PG-E1: prostaglandin E1; PRP: platelet-rich plasma; SNP: sodium nitroprusside; VASP: vasodilator-stimulated phosphoprotein